Featured Article: Trajectories of Posttraumatic Stress Symptoms in Parents of Children With a Serious Childhood Illness or Injury. (24th May 2018) - Muscara, Frank; McCarthy, Maria C; Hearps, Stephen J C; Nicholson, Jan M; Burke, Kylie; Dimovski, Anica; Darling, Simone; Rayner, Meredith; Anderson, Vicki A
Abstract: Objective: Serious childhood illness is associated with significant parent psychological distress. This study aimed to (a) document acute and posttraumatic stress symptoms (PTSS) in parents of children with various life-threatening illnesses; (b) identify trajectory patterns of parental PTSS and recovery over 18 months; (c) determine psychosocial, demographic, and illness factors associated with trajectory group membership. Methods: In total, 159 parents (115 mothers, 44 fathers) from 122 families participated in a prospective, longitudinal study that assessed parent psychological responses across four time points—at diagnosis, and 3, 6, and 18 months later. Children were admitted to the Cardiology, Oncology, and Pediatric Intensive Care Departments in a tertiary pediatric hospital. The primary outcome was parent PTSS. Results: Three distinct parent recovery profiles were identified—"Resilient, " "Recovery, " and "Chronic." The "Resilient" class (33%) showed low distress responses across the trajectory period, whereas the "Recovery" class (52%) showed significantly higher levels of distress at the time of diagnosis that gradually declined over the first months following their child's illness. Both of these classes nevertheless remained within the normative range throughout. In contrast, the "Chronic" class (13%) was consistently high in severity, remaining within the clinical range across the entire period. Psychosocial factors such as mood, anxiety, and emotional responses predicted group membership, whereas demographic and illness factors did not. Conclusions: Parents show considerable resilience in the face of children's life-threatening illnesses. Early assessment of parent psychosocial factors may aid identification of those who would benefit from early intervention.